2003
DOI: 10.5301/jva.2008.3680
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge of the Anomalies of the Big Central Veins Reduces the Morbidity during the Cannulation for Hemodialysis: Description of a Case of Persistent Left Superior Vena Cava and Revision of Literature

Abstract: The persistence of a left superior vena cava is the result of a lack of an embryological involution of the left anterior cardinal vein. This anomaly is very rare: about 0.3% of the general population. Its incidence increases remarkably from 3-10% in those patients affected with congenital heart disease. Described herein is a case of persistent left superior vena cava, discovered by chance, following the placement of a central venous catheter for hemodialysis. A chest X-ray in projection back-forward showed the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The most common subtype of persistent left SVC results in the presence of both left and right SVCs 8,9 . More rarely, abnormalities of the embryological development lead to an absent right SVC with persistent left SVC, as previously described in both pediatric and adult patients [10][11][12][13][14][15][16] . In most cases, persistent left SVC drains into the right atrium via the coronary sinus with of no hemodynamic consequence 17 .…”
Section: Discussionmentioning
confidence: 78%
“…The most common subtype of persistent left SVC results in the presence of both left and right SVCs 8,9 . More rarely, abnormalities of the embryological development lead to an absent right SVC with persistent left SVC, as previously described in both pediatric and adult patients [10][11][12][13][14][15][16] . In most cases, persistent left SVC drains into the right atrium via the coronary sinus with of no hemodynamic consequence 17 .…”
Section: Discussionmentioning
confidence: 78%
“…6 There were not any vascular or perivascular traumatic complications associated with the procedure of catheter insertions, and only one catheter related complication, which was arrhythmia, was reported. 7 Catheters provided good blood flow in all patients after successful catheter placement throughout the course of case presentations. The durations of catheter use for hemodialysis were not provided in all, but ranged from 4 weeks to 15 months where available.…”
Section: Discussionmentioning
confidence: 98%
“…Dionisio et al reported a case with PLSVC who developed clinically significant arrhythmia following catheter placement; hence they suggested that catheters should be removed immediately once PLSVC has been recognized. 7 However, arrhythmia can also occasionally occur in patients with normal venous anatomy of the thorax and it may be due to an inappropriate extension of the catheter tip into the right atrium. 9 In such cases, we attempt a slight withdrawal of the catheter, which has terminated arrhythmia almost in all patients.…”
Section: Discussionmentioning
confidence: 99%
“…7 Use of PLSVC as hemodialysis access was also associated with some complications, including arrhythmia, pericardial effusion, thrombus formation, and reduced blood flow to the heart. 7,[15][16][17] However, literature reviews of the same case show the possibility of PLSVC being used as hemodialysis access in short-and long-term hemodialysis patients, certainly with tighter monitoring. 7,14 Management of CVC malposition must be based on several considerations: the indication of insertion, the location of insertion, and the condition of the patient.…”
Section: Discussionmentioning
confidence: 99%